Polyarteritis nodosa clinically mimicking nonocclusive mesenteric ischemia - Shirai, Tsuyoshi (Baishideng Publishing Group Co., Limited, 2013)
Here, we present the case of a 74-year-old Japanese man with segmental intestinal necrosis, which developed after treatment with pulsed methylprednisolone for mononeuritis multiplex. The patient was weakly positive for myeloperoxidase (MPO)-anti-neutrophil cytoplasmic antibody (ANCA). Computed tomography and surgical findings were compatible with nonocclusive mesenteric ischemia (NOMI). He underwent small intestinal resection by emergency surgery and an intestinal fistula was made. Pathologically, necrotizing vasculitis with fibrinoid necrosis was present in medium to small-sized arteries, which was equivalent to Arkin’s classification II-IV. Most of the arteries had fibrous intimal thickening, which was considered to obstruct the arteries and thus cause segmental intestinal necrosis. A diagnosis of polyarteritis nodosa (PAN) was made, and intravenous cyclophosphamide pulse therapy was added to the therapeutic regimen. This patient was successfully treated with these multidisciplinary therapies and his stoma was finally closed. This is a very rare and indicative case of PAN weakly positive for MPO-ANCA and clinically mimicking NOMI, which occurred even after treatment with pulsed methylprednisolone.